Biblical Study of Jesus Christ’s Leadership in John’s Gospel and Its Application at GPdI Betesda Kabanjahe - Eliezer Andelta Sinukaban (International Journal of Christian Education and Philosophical Inquiry, 2025)
In the contemporary Christian context, many churches face a leadership crisis marked by corruption, arrogance, lack of integrity, and resistance to criticism—traits that starkly contrast with the servant-hearted leadership exemplified by Jesus Christ. This study aims to explore the biblical foundation of Jesus’ leadership, both in character and technical dimensions, as portrayed in the Gospel of John, and to examine its implementation within GPdI Betesda Kabanjahe. Employing a qualitative methodology, the research integrates two primary approaches: a theological-biblical analysis and a case study of leadership practices in the local church. The theological dimension focuses on Jesus as the Good Shepherd, emphasizing relational depth, sacrificial service, and intentional character formation of His disciples. The case study approach investigates how these principles are understood and applied by church leaders in GPdI Betesda. Findings reveal two key insights. First, the pastoral leadership model in the Gospel of John presents Jesus as a shepherd who leads through personal connection, selfless sacrifice, and transformative discipleship. While these values are normatively acknowledged by church leaders, their practical application in GPdI Betesda remains partial and lacks systemic integration into the church’s organizational and ministerial structures. Second, pastoral leadership at GPdI Betesda is marked by exemplary behavior and love in service. However, inconsistencies persist in leadership stability, spiritual maturity, and character development. The absence of structured ministry management and leadership formation contributes to these gaps. In conclusion, the study underscores the need for churches to realign leadership practices with the biblical model of Jesus, fostering integrity, humility, and servant leadership. Strengthening character development and implementing structured leadership systems are essential steps toward resolving the leadership crisis and embodying Christ-like shepherding in the church context.